NURSING: SPIRITUAL CARE OF THE ONCOLOGY PATIENT, FROM AN INTEGRATIVE REVIEW - Castañeda León, Karin (2024)
Objective: The purpose of this study was to describe the evidence available in the scientific literature regarding the spiritual care provided by nurses to oncology patients, analyzed from a palliative care perspective. Methods: An integrative review of the literature was carried out using six databases: Redalyc, ScienceDirect, BVS, Scielo, PubMed and Google Scholar, published in the period 2018-2022. The data were collected during the months of August to November 2022, following the guidelines established by the PRISMA method. Results: 14 publications were considered, whose textual analysis allowed the construction of four main themes: Spiritual/religious needs, Concretizations of Spiritual Nursing Care, Reflections on Spiritual Care and Barriers or gaps to implement spiritual care. Conclusion: The study verified the relevance of the spiritual dimension during the care of oncology patients and the need to promote the inclusion of the spiritual approach in care practices.